2015
DOI: 10.1890/es14-00303.1
|View full text |Cite
|
Sign up to set email alerts
|

Burning reveals cryptic plant diversity and promotes coexistence in a California prairie restoration experiment

Abstract: Abstract. Grassland and prairie restoration projects in California often result in long-term establishment of only a few native plant species, even when they begin with a diverse seed palette. One explanation for the disappearance of certain native species over time is that they are excluded through competition. If so, management that reduces interspecific competition may favor ''subordinate'' natives and promote greater native species diversity in restored communities. Potential management approaches to accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…In this same system, priority effects were weaker when no rainfall occurred in the interval between sowing of early‐ and late‐arriving guilds (Vaughn & Young ). These results, and a watering experiment done in this system (Young et al ), suggest that, in our study, water availability limited the ability of guilds sown early to preemptively utilize niche space and establish priority.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In this same system, priority effects were weaker when no rainfall occurred in the interval between sowing of early‐ and late‐arriving guilds (Vaughn & Young ). These results, and a watering experiment done in this system (Young et al ), suggest that, in our study, water availability limited the ability of guilds sown early to preemptively utilize niche space and establish priority.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, two of the four publications in Table S2 that monitored priority experiments for more than one season suggested that the priority effects were short-lived. One long-term study of spatial aggregation as a priority technique also showed only temporary benefits (Porensky et al 2012;Young et al 2015aYoung et al , 2015b. It is noteworthy, however, that one of the multi-year studies actually showed an increase in priority effect through time (Vaughn & Young 2015).…”
Section: Implications For Restorationmentioning
confidence: 99%
“…, Young et al. ). Practitioners should also be mindful that the advantages of priority may result in lower cover of late‐arriving dominant species (e.g., S. pulchra , L. formosus ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional management strategies may be required to increase presence and abundance of these more subordinate species: e.g., grazing, mowing, prescribed fire, summer irrigation, and interspecific aggregation (Hayes and Holl 2003, Wainwright et al 2012, Funk et al 2015, Young et al 2015a. Practitioners should also be mindful that the advantages of priority may result in lower cover of late-arriving dominant species (e.g., S. pulchra, L. formosus).…”
Section: Implications For Managementmentioning
confidence: 99%
“…Disturbance can influence these processes to ultimately affect a and b diversities by affecting environmental heterogeneity both within and among sites (Clough et al 2007). For example, disturbances such as fire and grazing can create patchiness in environmental conditions within sites which can have positive effects on a diversity by creating refuges and suppressing the dominant species (Sousa 1984, van Klink et al 2015, Young et al 2015. The positive effect of environmental heterogeneity on a diversity has been observed in many different systems for taxonomic groups including plants (Adler et al 2001, Anderson et al 2004, insects (Hendrickx et al 2007), fish (Lepori et al 2005), and birds (Fuhlendorf et al 2006, Hovick et al 2015.…”
Section: Introductionmentioning
confidence: 99%